La Tecnología Del Desempeño Humano Y Cómo Influye En La Mejora Del Desempeño De Las Organizaciones, Una Reflexión Sobre Los Modelos De Procesos - Rodríguez, Jesús Manuel Gutiérrez; Leyva, Ernesto Alonso Lagarda (European Scientific Journal, ESJ, 2016)
The present study explains the different models of performance improvement based on the Human Performance Technology (HPT) model, which is a diagnostic and strategy tool to increase organizational effectiveness in the workplace. The conceptual elements are based on studies conducted by the International Society for Performance Improvement (ISPI). Therefore, it is concluded that it is possible to know the fundamental characteristics of a model to improve organizational performance including the detection requirements of opportunity areas in an organization.